A direct method to access various functional arylalkoxysilanes by Rh-catalysed intermolecular C–H silylation of alkoxysilanes. Issue 36 (30th August 2022) - Som, Salina; Choi, Jongwook; Katsoulis, Dimitris; Lee, Kangsang L.
Abstract : The control of alkoxysilane redistribution enables the direct access of functional arylalkoxysilanes by Rh-catalyzed C–H silylations. Abstract : Efficient protocols for intermolecular C–H silylations of unactivated arenes and heteroarenes with HMe2 SiOEt are disclosed. The silylations are catalysed by a Rh-complex (0.5 mol%) derived from commercially available [Rh(coe)2 Cl]2 and ( S, S )-Ph-BPE in the presence of cyclohexene at 100 °C, furnishing desired arylethoxydimethylsilanes up to 99% yield. The regioselectivity is mainly affected by the steric bulk of the substituents in arenes and by electronic effects as an ancillary factor. Mechanistic study revealed that the mono-hydrido dimeric Rh-complex, [Rh2 (Ph-BPE)2 (μ-H)(μ-Cl)], is an active catalytic intermediate, which further suppresses the formation of redistribution byproducts in the silylation. Preliminary results show that the current protocol can be extended to double C–H silylations affording bis-silylated arenes and is applicable to the silylation of HMeSi(OEt)2 to deliver the corresponding (aryl)SiMe(OEt)2 .